Antioxidants: What are they and what role do they play in physical activity and health? - Clarkson, P. M. (1996)
- Exercise and Oxidative Stress: How is it Detected? - Effects of Exercise, Training, and Antioxidant Supplementation - Vitamin Supplementation and Exercise Performance - Antioxidant Status of Athletes - Recommendations for Antioxidant Use by Athletes